PRAANGGAPAN DALAM NOVEL MAHAMIMPI ANAK NEGERI KARYA SUYATNA PAMUNGKAS - Juliani, Nur Helda; Burhanudin, Dudung; ', Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The study, entitled presuppositions in the novel Mahamimpi Anak Negeri by Suyatna pamungkas. The purpose of this research is to determine the presuppositions in the novel Mahamimpi Anak Negeri by Suyatna pamungkas on the forms and meanings in the novel. The method in this research is analytical descriptive method with qualitative approach. In this research, writer use data technique accumulation by notation and documentation. Data of this study are 65 data.Data form the research i have found in the study is the presuppositions that the forms and meanings, presuppositions verbal form containing statement consists of one data, presuppositions implicature verbal form consists of eighteen data, presuppositions verbal form which replace the state consists of eight data, presuppositions shaped repetition consists of sixteen data, presuppositions shape composed of three said the time of data, presuppositions form a sentence that no topic or focus consists of three data and presuppositions form of a question consists of sixteen data.Key words: presuppositions, form and meaning, novel.